Maßgeschneiderte Halbzeuge - Umformtechnische Herstellung von Funktionsbauteilen zur Realisierung von Leichtbaukomponenten - Hetzel, Andreas; Schulte, Robert Karl; Vogel, Manfred; Degner, Julia; Merklein, Marion (wt Werkstattstechnik - Online, 2019)
Sheet Bulk Metal Forming enables the efficient manufacturing of functional lightweight components with different functional elements in a combined single stage deep drawing and upsetting process. By investigating the forming results with a conventional blank, regarding the properties like grain structure and Vickers hardness distribution, process limitations such as buckling and folding can be detected. These failures occur due to a three-dimensional stress and strain state as well as an insufficient die filling. A significant improvement of the quality of the produced parts can be enabled by the use of Tailored Blanks in the investigated process chain. With the manufacturing of the semi-finished parts by orbital forming, an adapted material pre-distribution can be realized, thus improving the die filling followed by a decrease of the parts' failures. Current research at the Institute of Manufacturing Technology focuses on the extension of the applicability of Tailored Blanks.
CRIS-Team Scopus Importer:2020-02-21